Granting Authority to Villages in the Context of Regional Autonomy Based on the Implementation of Law Number 6 of 2014 Concerning Villages - Abazis Subekti, Dzikri (Yayasan Mentari Madani, 2024)
Law Number 6 of 2014 concerning Villages has become the initial barometer of villages in remapping village authority, all government affairs that are the authority of the Regency / City which are handed over to the Village are government affairs that can directly improve services and community empowerment. In carrying out the implementation of Village Government, Village Development, Village Community Development, and Village Community Empowerment, Village Government requires authority in its implementation, both original authority and attributive authority. Where these authorities aim to encourage initiatives, movements, and participation of village communities for the development of village potentials and assets for mutual welfare to realize the goals of regional autonomy